Injury, illness and performance decrement in British national squad triathletes: A prospective study - Vleck, V.; Bentley, D. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Injury and illness incidence and possible antecedents, were assessed in 57 British National Squad Olympic distance (OD) triathletes via a 7-month prospective training diary study, running from February 1 up to World Championships (WC). The athletes spent 6.1 +- 2.5 weeks in `endurance base` training, 3.9 +- 3.1. weeks in `transition` training, 4.4 +- 3.3 weeks in `pre-competition` training and 4.9 +- 2.5 weeks in `competition` training in the lead-up to their National Championships, in week 21. All athletes obtained a top-50 placing at National Championships either within the study period or the preceding year. Return rates for the diaries were 43, 38, 33, 26, 21, 14 and 11 for each consecutive month of the study. Sixty three percent of the athletes reported at least one `performance decrement` (PD), and all were either injured or ill (according to the athletes` self-assessment) at least once, over the study period. In total, 95.8% of athletes sustained illness and 80.4% sustained injury- this coincided with PD in 34.0% and 60.0%, respectively. Illness, injury and PD occurred concurrently, at least once, in 24%. In a further 14%, at least one PD, with no report of injury or illness within a week of the incident, was observed. The proportion of athletes experiencing new overuse injury, new overuse injury and injury recurrence, or just injury recurrence, decreased from February to August (ns). A total of 1.25-1.72 anatomical sites were affected in each athlete in each month. However, 14.3- 53.8% of the injuries reported by each individual were between a second and a fifth occurrence to the same anatomical site. The case rates for new injury, and for new and recurring injury, respectively, were 10.0 - 27.6, and 17.5 - 58.0 per 1000 training hours of month specific training. The time that each athlete was affected by injury, including recurrences, was, 12.78 +- 7.5 days for calf injury, 10.5 +- 0.0 days for lower back injury, 7.63 +- 2.7 days for knee injury, 5.57+- 1.0 days for anterior thigh injury, and 6.18 +- 2.7 days for posterior thigh injury. Logistic regression analysis indicated that the athletes decreased their overall weighted training load (for five training intensity levels) in the weeks that new overuse injury occurred. It appears that their usual response to injury was to modify rather than stop their training. For over 50% of the weeks covered by the study, the % of respondents who did all or part of one session in cycle levels 1-4 or run levels 1-4 was lower in the injured athletes than in the group overall. Our results confirm that injury, and the recurrence of that injury, affects a large proportion of National Squad OD triathletes. However, to what extent the athletes` triathlon training is subsequently modified; as well as whether any PD associated with injury is due to that injury, to concomitant illness, or to both injury and illness, is not always clear. Few injury studies have either noted, or taken this effect into account.